Evaluating the validity of self-reported smoking in Mexican adolescents - James F Thrasher; Mauricio Hernandez-Avila; Luz Myriam Reynales-Shigematsu; Tonatiuh Barrientos-Gutiérrez; Eduardo Lazcano-Ponce; María del Carmen Valladolid-López; Ingris Peláez-Ballestas (BMJ Open)
Objectives We aimed to evaluate the validity of the self-reported smoking indicator used in the Global Youth Tobacco Survey (GYTS).Setting 43 middle and high-school classrooms from 26 schools were selected from Mexico City and Cuernavaca, Morelos.Participants A total of 1257 students provided both a questionnaire and a urine sample.Primary and secondary outcome Sensitivity and specificity of self-reported smoking compared to urinary cotinine. Validity indices were evaluated by subgroups of gender, social acceptability of smoking (ie, smoking parents or friends) and smoking frequency.Results Sensitivity and specificity for current smoking were 93.2% and 81.7%, respectively. Validity indices remained stable across gender. Parental smoking status moderated the validity of self-report, which had lower sensitivity in adolescents with non-smoking parents (86.7%) than in adolescents with smoking parents (96.6%). Sensitivity and specificity increased with smoking frequency.Conclusions This first validation study of self-reported current smoking used in the GYTS among Mexican adolescents suggests that self-reported smoking in the past 30 days is a valid and stable indicator of current smoking behaviour. This measure appears suitable for public health research and surveillance.